Peningkatan Kepatuhan Wajib Pajak melalui Penerapan Sistem e-filling yang Dimoderasi oleh Pemahaman Internet - Aminudin, Moch; Ali, Ali; Subadriyah, Subadriyah (Universitas Islam Negeri Sunan Kudus, 2019)
Taxes are the largest source of state revenue that has many roles. Until 2017 taxes can contribute 85.6% of state revenues. The level of taxpayer compliance in Indonesia is quite alarming and continues to decline, in 2011 taxpayer compliance could reach 97.2%, but in 2014 it fell to 91.6%, and again in 2015 only 82%. The purpose of this study was to determine the effect of the implementation of the efilling system on taxpayer compliance and to know the relationship between the application of e-filling systems and taxpayer compliance which was moderated by internet understanding. The initial step as the main basis of research is by collecting data. Primary data obtained from the distribution of questionnaires. All taxpayers registered with the Tax Office as the study population. Determination of the sample was obtained by the Slovin formula so that 100 respondents were obtained. The analysis method uses simple linear regression and the Moderated Regression Analysis (MRA) method. The results obtained are that the application of e-filling system has a significant effect on taxpayer compliance and internet understanding is able to moderate the relationship between the application of e-filling systems to taxpayer compliance.